2018
DOI: 10.1016/j.envpol.2018.05.052
|View full text |Cite
|
Sign up to set email alerts
|

The temporal variation of SO2 emissions embodied in Chinese supply chains, 2002–2012

Abstract: Whilst attention is increasingly being focused on embodied pollutant emissions along supply chains in China, relatively little attention has been paid to dynamic changes in this process. This study utilized environmental extended input-output analysis (EEIOA) and structural path analysis (SPA) to investigate the dynamic variation of the SO emissions embodied in 28 economic sectors in Chinese supply chains during 2002-2012. The main conclusions are summarized as follows: (1) The dominant SO emission sectors dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 57 publications
(57 reference statements)
2
10
0
Order By: Relevance
“…During the study period, the total SO 2 emissions increased from 25.8 Mt (million tons) in 2007 to 26.4 Mt in 2010 and then decreased to 22.5 Mt in 2012, consistent with the results obtained by Yang et al (2018a). Figure S24 illustrates the production-and consumption-based SO 2 emissions in 2007, 2010, and 2012, and also shows that the production-based emissions were higher than the consumption-based emissions in most provinces since a large part of emissions embodied in consumption leaked to the RoW.…”
Section: Production-and Consumption-based So 2 Emissionssupporting
confidence: 89%
“…During the study period, the total SO 2 emissions increased from 25.8 Mt (million tons) in 2007 to 26.4 Mt in 2010 and then decreased to 22.5 Mt in 2012, consistent with the results obtained by Yang et al (2018a). Figure S24 illustrates the production-and consumption-based SO 2 emissions in 2007, 2010, and 2012, and also shows that the production-based emissions were higher than the consumption-based emissions in most provinces since a large part of emissions embodied in consumption leaked to the RoW.…”
Section: Production-and Consumption-based So 2 Emissionssupporting
confidence: 89%
“…Liu & Wang, 2015, 2017bY. Lu et al, 2019;Haikun Wang et al, 2017;X. Yang, Zhang, Fan, Li, & Meng, 2018;X.…”
Section: Accepted Articlementioning
confidence: 99%
“…Given the large variations between Chinese regions or sectors, the contributions of drivers to emissions change were evaluated for some specific regions or sectors, such as coal‐fired power plants (Li et al., 2020; Wu et al., 2019), iron and steel industry (Mao et al., 2013), industrial sector (Hang et al., 2019; Liu & Wang, 2017a; W. Zhang et al., 2015), and the three key regions (i.e., the Beijing‐Tianjin‐Hebei region, the Yangtze River Delta region, and the Pearl River Delta region) where Air Pollution and Control Action Plan promulgated in 2013 focused on (Q. Zhang et al., 2019). Recognizing the emission reduction potential from a consumption perspective, some studies also focus on the air pollution emissions transfer (Huo et al., 2014; Li et al., 2019; Liu & Wang, 2015, 2017b; Y. Lu et al., 2019; H. Wang et al., 2017; Yang, Zhang, Fan, Li, & Meng, 2018; Yang, Zhang, Fan, Yu, & Zhao, 2018; H. Y. Zhao et al., 2015), inequity (F. Wang et al., 2020; X. Yang et al., 2019; Zhang, Liu, et al., 2018; Zhang, Wang, et al., 2018), and drivers induced by international and inter‐regional trade (Chen et al., 2020; Guan et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to optimize PAH mitigation strategies, it is essential to reallocate the responsibilities of production-related pollutants in economic sectors based on final consumption or primary input with an environmentally extended input–output analysis (EEIOA). Several studies have applied EEIOAs to investigate embodied emissions from the consumption side, including CO 2, SO 2, PM 2.5, mercury, and other toxic compound emissions. , For instance, Ou et al found that an increase in Chinese non-methane volatile organic compound emissions of 3.5 million tons in 2013 was associated with final consumption. However, relatively little attention has been paid to enabled emissions from the supply side even though it has been reported that primary input behavior may have great potential to reduce emissions. , In terms of PAHs’ environmental behavior, various studies have focused on distribution patterns, source apportionment, ,, and emission inventory. ,,, However, no previous research has employed an EEIOA on the PAH emission inventory in China despite the significant human and economic costs of these pollutants.…”
Section: Introductionmentioning
confidence: 99%